Letter from Lieut. Com'dr J. D. Marvin to James Curtis Booth, September 2, 1873 - Marvin, J. D. (1873)
Lieutenant Commander J. D. Marvin writes to James Curtis Booth (1810-1888) with questions concerning the ability of copper to absorb oxygen.
Keywords: Booth, James Curtis, 1810-1888; Copper--Properties; Copper; Chemistry; Marvin, J. D.